CdS thin film material and preparation method and application thereof
Preparation of CdS films by hydrothermal method solves the problems of high equipment requirements and low film quality in the prior art, and the preparation of high-purity and good crystalline films is achieved, and the photocatalytic degradation efficiency and piezoelectric properties are improved.
Patent Information
- Application Number
- CN202411636266.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
AI Technical Summary
The existing CdS film preparation methods have problems such as high equipment requirements, low film quality and performance, and it is difficult to effectively improve the performance of photocatalytic degradation of organic matter.
The CdS film was prepared by hydrothermal method, and a high-purity and good crystallinity CdS film was obtained by performing a hydrothermal reaction between 100°C and 120°C in an autoclave.
The preparation of CdS films with high purity and good crystallinity is achieved, which reduces energy consumption and preparation costs, improves the efficiency of photocatalytic degradation of organic matter, and also has piezoelectric properties.
Smart Images

Figure CN119530946A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and in particular relates to a CdS thin film material and a preparation method and application thereof. Background Art
[0002] Photovoltaic materials are clean energy materials that collect solar energy and convert it into electrical energy. Photovoltaic materials have both the stability of electronic materials and the advancement of photonic materials. They will be widely used in the optoelectronic era and have great development prospects. However, solar energy is an intermittent energy source, and its collection is limited to sunrise and sunset. Therefore, how to collect other energy in the dark to break the limitation that solar energy can only be collected during the day will be a topic that we have to face in the future. However, the world is magical, and the magical world has given some materials magical properties. Some sulfide semiconductor nanomaterials not only have excellent photoelectric conversion properties, can collect solar energy and convert it into electrical energy, but also have very excellent piezoelectric properties, can collect mechanical energy and convert it into electrical energy. This provides a new idea for the research of solar cells - the photoelectric and piezoelectric properties of these materials can be used at the same time, so that these materials can not only collect solar energy and convert it into electrical energy at sunrise, but also collect pressure generated by wind, tides, and moving cars at night and convert them into electrical energy, thereby effectively supplementing the limitation that solar cells can only collect solar energy at sunrise.
[0003] At present, the scientific community generally recognizes that TiO 2 , WO 3 , ZnO and CdS, among which, although CdS has certain photocorrosiveness compared with other photocatalysts, it has a suitable bandgap width (2.42eV), and is an N-type semiconductor, which absorbs in both the ultraviolet and visible light regions, and has high photocatalytic efficiency, making it an ideal industrial photocatalyst. The semiconductor sulfide CdS not only has excellent photocatalytic performance, but also has very excellent piezoelectric properties, which can collect mechanical energy and convert it into electrical energy. The existing CdS film preparation methods mainly include radio frequency magnetron sputtering, near-space sublimation, chemical water bath method (CBD) and spin coating, among which radio frequency magnetron sputtering and near-space sublimation are physical methods with extremely high requirements on equipment, and the chemical water bath method has many defects, and the quality and performance of the film are not high. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a CdS thin film material and its preparation method and application. The present invention proposes a piezoelectrically enhanced CdS photocatalyst with synergistic effects of photoelectricity and piezoelectricity - CdS thin film, which provides a simpler and more effective method for improving the performance of photocatalytic degradation of organic matter.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for preparing a CdS nano single crystal thin film material comprises the following steps:
[0007] The cadmium-containing precursor solution is adsorbed on the substrate, and impurities are removed to obtain the cadmium-containing substrate.
[0008] The cadmium-containing substrate is placed in a sulfur-containing precursor solution to cause a precipitation reaction, and impurities are removed to obtain a substrate containing CdS seed crystals on the surface.
[0009] The cadmium-containing precursor solution and the sulfur-containing precursor solution are mixed, and then added to the substrate containing the CdS seed crystals for hydrothermal reaction, and a CdS thin film material is obtained through post-treatment.
[0010] The present invention proposes a piezoelectrically enhanced CdS photocatalyst with synergistic effects of photoelectricity and piezoelectricity, namely, a CdS film. First, a substrate with CdS seed crystals on the surface is prepared, and the substrate containing the CdS seed crystals is subjected to a hydrothermal reaction in a cadmium-containing precursor solution and a sulfur-containing precursor solution to obtain a CdS film material. The present invention can effectively reduce the introduction of external impurities through the hydrothermal method, thereby preparing a high-purity cadmium sulfide film, and during the reaction process, high temperature conditions are conducive to the growth and crystallization of crystals, so that the prepared cadmium sulfide film has good crystallinity. In addition, by adjusting the reaction conditions, the morphology of the cadmium sulfide film can be effectively controlled to meet the needs of different application scenarios. The hydrothermal method can enable the reaction to be carried out in a relatively uniform environment, which is conducive to the preparation of a uniform cadmium sulfide film.
[0011] Compared with some high-temperature preparation methods, the reaction temperature of the hydrothermal method of the present invention is relatively low, which is 100°C to 120°C, which can reduce energy consumption and preparation costs, and also avoid high temperature damage to the substrate material, expanding the selection range of the substrate material. In addition, the experimental equipment and operation process of the hydrothermal method are relatively simple, and do not require complex vacuum equipment and expensive raw materials. It is only necessary to put the reactants into an autoclave and react at a certain temperature and pressure. The raw materials used in the present invention are inorganic salts and water, which are relatively cheap, and no expensive equipment and special gas protection are required during the reaction process, so the preparation cost is low; the reaction process produces fewer pollutants and has less impact on the environment.
[0012] In a preferred embodiment of the present invention, the hydrothermal treatment temperature is 100° C. to 120° C., and the hydrothermal treatment time is 6 h to 8 h.
[0013] In a preferred embodiment of the present invention, the cadmium-containing precursor solution is a cadmium acetate dihydrate solution.
[0014] In a preferred embodiment of the present invention, the concentration of the cadmium-containing precursor solution is 0.005 mol / L to 0.01 mol / L.
[0015] In a preferred embodiment of the present invention, the sulfur-containing precursor solution is an aqueous solution of thioacetamide.
[0016] In a preferred embodiment of the present invention, the concentration of the sulfur-containing precursor solution is 0.005 mol / L to 0.01 mol / L.
[0017] In a preferred embodiment of the present invention, the volume ratio of the cadmium-containing precursor solution to the sulfur-containing precursor solution is 1:1 to 1.5.
[0018] In a preferred embodiment of the present invention, the substrate is conductive glass, a silicon substrate or a polymer flexible substrate.
[0019] Another object of the present invention is to provide a CdS thin film material prepared by any of the preparation methods described above.
[0020] The third object of the present invention is to provide an application of the above-mentioned CdS thin film material in photocatalytic degradation of organic matter.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention proposes a piezoelectrically enhanced CdS photocatalyst with synergistic effects of photoelectricity and piezoelectricity, namely, a CdS film. First, a substrate containing CdS seeds on the surface is prepared, and the substrate containing CdS seeds is subjected to a hydrothermal reaction in a cadmium-containing precursor solution and a sulfur-containing precursor solution to obtain a CdS film material. The present invention can effectively reduce the introduction of external impurities through the hydrothermal method, thereby preparing a high-purity cadmium sulfide film, and during the reaction process, high temperature conditions are conducive to the growth and crystallization of crystals, so that the prepared cadmium sulfide film has good crystallinity. In addition, by adjusting the reaction conditions, the morphology of the cadmium sulfide film can be effectively controlled to meet the needs of different application scenarios. The hydrothermal method can enable the reaction to proceed in a relatively uniform environment, which is conducive to the preparation of a uniform cadmium sulfide film.
[0023] 2. Compared with some high-temperature preparation methods, the reaction temperature of the hydrothermal method of the present invention is relatively low, which is 100°C to 120°C, which can reduce energy consumption and preparation costs, and also avoid high temperature damage to the substrate material, expanding the selection range of the substrate material. In addition, the experimental equipment and operation process of the hydrothermal method are relatively simple, and do not require complex vacuum equipment and expensive raw materials. It is only necessary to put the reactants into an autoclave and react at a certain temperature and pressure. The raw materials used in the present invention are inorganic salts and water, which are relatively cheap, and no expensive equipment and special gas protection are required during the reaction process, so the preparation cost is low; the reaction process produces fewer pollutants and has less impact on the environment.
[0024] 3. The CdS photocatalytic nanomaterial prepared by the present invention has superposition of piezoelectric and photoelectric effects, that is, the holes generated by the piezoelectric effect and the holes generated by the photoelectric effect are superimposed on each other, and the electrons generated by the piezoelectric effect and the electrons generated by the photoelectric effect are superimposed on each other. Such dual effects can increase the number of electrons and holes on the surface of CdS, and are expected to significantly improve its photocatalytic degradation efficiency. Two functions, namely photovoltaic and piezoelectric properties, can be realized on the same CdS film at the same time, thereby integrating the piezoelectric and photoelectric conversion properties of semiconductors to achieve integrated applications in the fields of piezoelectricity and photovoltaics.
[0025] 4. Compared with other methods, the hydrothermal method for preparing CdS thin film in the present invention is simple in experimental operation and low in cost. The prepared thin film has many advantages, such as high purity, good crystallization, controllable morphology, low stress, strong adhesion to the substrate, etc. The CdS thin film material prepared by the present invention has a fading rate of 90.1% in 30 minutes in a methyl orange solution with a concentration of 10 mg and a pH value of 6.0 under the irradiation of a 365nm ultraviolet lamp in the laboratory and on a vibrating screen with a vibration frequency of 147 times / min, which is higher than the fading rate of 74.6% under the same vibration conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the CdS film prepared in Example 1 of the present invention.
[0027] Figure 2 This is the XRD characterization result of the cadmium sulfide film prepared in Example 1 of the present invention.
[0028] Figure 3 This is the surface element scanning result of the cadmium sulfide film prepared in Example 1 of the present invention characterized by EDS.
[0029] Figure 4 This is a schematic diagram of the principle of implementing the piezoelectric-photoelectric degradation of methyl orange in the present invention.
[0030] Figure 5 This is a current response diagram of the piezoelectric-photoelectric performance test of the cadmium sulfide film prepared in Example 1 of the present invention.
[0031] Figure 6 This is a graph showing the fading rate of methyl orange degradation by the CdS film prepared in Example 1 of the invention. DETAILED DESCRIPTION
[0032] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0034] Example 1
[0035] A method for preparing a CdS thin film comprises the following steps:
[0036] (1) 0.005 mol / L cadmium acetate dihydrate aqueous solution (Cd(OAc) 2 ·2H 2 O) adsorbs on a conductive glass substrate to obtain a conductive glass substrate on which cadmium is adsorbed.
[0037] (2) The conductive glass substrate adsorbed with cadmium is dissolved in deionized water, and the excess ions other than Cd ions are removed with deionized water to obtain a cadmium-containing conductive glass substrate.
[0038] (3) The cadmium-containing conductive glass substrate from which the excess ions were removed in step (2) was placed in a 0.005 mol / L thioacetamide aqueous solution (CH 3 CSNH 2 ) is adsorbed and a precipitation reaction occurs to obtain a conductive glass substrate adsorbed with sulfur.
[0039] (4) Dissolving the conductive glass substrate adsorbed with sulfur in deionized water, removing excess ions other than S ions, and obtaining CdS seed crystals on the substrate surface.
[0040] (5) After 15 mL of cadmium acetate dihydrate solution and 15 mL of thioacetamide aqueous solution were stirred continuously for 8 min at room temperature, they were mixed and transferred together with the CdS seed crystal substrate into a 50 mL polytetrafluoroethylene-lined autoclave for hydrothermal treatment at 100 °C for 6 h. The autoclave was then naturally cooled to room temperature and the substrate was washed several times with anhydrous ethanol and deionized water to obtain a CdS film with a thickness of about 2.5 μm.
[0041] Example 2
[0042] A method for preparing a CdS thin film comprises the following steps:
[0043] (1) 0.008 mol / L cadmium acetate dihydrate aqueous solution (Cd(OAc) 2 ·2H 2 O) adsorbs on a conductive glass substrate to obtain a conductive glass substrate on which cadmium is adsorbed.
[0044] (2) The conductive glass substrate adsorbed with cadmium is dissolved in deionized water, and the excess ions other than Cd ions are removed with deionized water to obtain a cadmium-containing conductive glass substrate.
[0045] (3) The cadmium-containing conductive glass substrate from which the excess ions were removed in step (2) was placed in a 0.008 mol / L thioacetamide aqueous solution (CH 3 CSNH 2 ) is adsorbed and a precipitation reaction occurs to obtain a conductive glass substrate adsorbed with sulfur.
[0046] (4) Dissolving the conductive glass substrate adsorbed with sulfur in deionized water, removing excess ions other than S ions, and obtaining CdS seed crystals on the substrate surface.
[0047] (5) After 15 mL of cadmium acetate dihydrate solution and 20 mL of thioacetamide aqueous solution were stirred continuously for 5 min at room temperature, they were mixed and transferred together with the CdS seed crystal substrate into a 50 mL polytetrafluoroethylene-lined autoclave for hydrothermal treatment at 110 °C for 7 h. The autoclave was then naturally cooled to room temperature and the substrate was washed several times with anhydrous ethanol and deionized water to obtain a CdS film with a thickness of about 2.5 μm.
[0048] Example 3
[0049] A method for preparing a CdS thin film comprises the following steps:
[0050] (1) 0.01 mol / L cadmium acetate dihydrate aqueous solution (Cd(OAc) 2 ·2H 2 O) adsorbs on a conductive glass substrate to obtain a conductive glass substrate on which cadmium is adsorbed.
[0051] (2) The conductive glass substrate adsorbed with cadmium is dissolved in deionized water, and the excess ions other than Cd ions are removed with deionized water to obtain a cadmium-containing conductive glass substrate.
[0052] (3) The cadmium-containing conductive glass substrate from which the excess ions were removed in step (2) was placed in a 0.01 mol / L thioacetamide aqueous solution (CH 3 CSNH 2 ) is adsorbed and a precipitation reaction occurs to obtain a conductive glass substrate adsorbed with sulfur.
[0053] (4) Dissolving the conductive glass substrate adsorbed with sulfur in deionized water, removing excess ions other than S ions, and obtaining CdS seed crystals on the substrate surface.
[0054] (5) After 15 mL of cadmium acetate dihydrate solution and 22.5 mL of thioacetamide aqueous solution were stirred continuously for 10 min at room temperature, they were mixed and transferred together with the CdS seed crystal substrate into a 50 mL polytetrafluoroethylene-lined autoclave for hydrothermal treatment at 120 °C for 8 h. The autoclave was then naturally cooled to room temperature and the substrate was washed several times with anhydrous ethanol and deionized water to obtain a CdS film with a thickness of about 2.5 μm.
[0055] Results Analysis
[0056] The present invention prepares nanocrystalline monolayer films on different substrates (such as FTO, ITO and flexible substrates, etc.), and uses an electrochemical workstation to measure photovoltaic and piezoelectric properties, and determines the voltage and current changes when photovoltaic and piezoelectricity occur simultaneously. The current size of the vibrating screen is about 1.5×10 -8 A, while under the condition of vibration and illumination, it is about 3.0×10 -8 A.
[0057] The morphology of the samples was analyzed by JEOL JSM-6701F cold field scanning electron microscope (FESEM), and the composition of the samples was analyzed by X-ray energy dispersive spectrometer (EDS, Sigma500). The crystal structure and phase composition of the samples were analyzed by RigaKa D / max-RB X-ray diffractometer (XRD), and CuKα The excitation source was 1.2° / min, and the scanning range was 20°~70°. The current response was measured using an electrochemical workstation (RST5200F). The methyl orange degradation experiment was tested using a 8100C UV-Vis spectrophotometer from Beijing Labtech Instrument Co., Ltd.
[0058] Figure 1 This is a SEM image of the cadmium sulfide film prepared in Example 1 of the present invention. It can be seen from the image that the surface of the prepared film is nanoparticles and the film thickness is about 2.5 microns, indicating that a thin film sample has been successfully prepared by the method of the present invention.
[0059] Figure 2 This is the XRD characterization result of the cadmium sulfide film prepared in Example 1 of the present invention. Obvious characteristic peaks can be seen from the figure, and the results show that the phase structure of the composite is a cubic phase.
[0060] Figure 3 This is the EDS spectrum of the cadmium sulfide film prepared in Example 1 of the present invention. From the figure, it can be seen that the Cd element and the S element are obviously present, and the result shows that the prepared film is CdS.
[0061] Figure 4This is a schematic diagram of the principle of implementing the piezoelectric-photoelectric degradation of methyl orange in the present invention. The figure shows an example process of organic degradation, indicating the implementation method of organic methyl orange degradation.
[0062] Figure 5 This is the current response diagram of the piezoelectric-photoelectric performance test of the cadmium sulfide film prepared in Example 1 of the present invention. It can be seen from the figure that the current magnitude is about 1.5×10 -8 A, while under the condition of vibration and illumination, it is about 3.0×10 -8 A. The results show that the current under vibration plus illumination increased by 1 times, indicating that a larger current can be generated under vibration plus illumination conditions, which can promote the photocatalytic effect.
[0063] Figure 6 This is a graph showing the degradation rate of methyl orange by the CdS film prepared in Example 1 of the present invention. It can be seen from the graph that the fading rate of methyl orange under the piezoelectric-photoelectric effect within 30 minutes is 90.1%, which is higher than the fading rate of 74.6% under the same vibration conditions. The results show that the degradation rate of methyl orange under the piezoelectric-photoelectric effect is significantly improved.
[0064] In summary, the CdS photocatalytic nanomaterial prepared by the present invention has the superposition of piezoelectric and photoelectric effects, that is, the holes generated by the piezoelectric effect and the holes generated by the photoelectric effect are superimposed on each other, and the electrons generated by the piezoelectric effect and the electrons generated by the photoelectric effect are superimposed on each other. Such a dual effect can increase the number of electrons and holes on the surface of CdS, and is expected to significantly improve its photocatalytic degradation efficiency. Two functions, namely photovoltaic and piezoelectric properties, are simultaneously realized on the same CdS film, so that the piezoelectric and photoelectric conversion properties of semiconductors can be integrated together to realize the integrated application in the fields of piezoelectricity and photovoltaics.
[0065] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0066] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a CdS thin film material, characterized in that: The following steps are involved: Adsorbing a cadmium-containing precursor solution on a substrate and removing impurities to obtain a cadmium-containing substrate; Placing the cadmium-containing substrate in a sulfur-containing precursor solution to cause a precipitation reaction, and removing impurities to obtain a substrate having CdS seed crystals on the surface; The cadmium-containing precursor solution and the sulfur-containing precursor solution are mixed, and then added to the substrate containing the CdS seed crystals for hydrothermal reaction, and a CdS thin film material is obtained through post-treatment.
2. The method for preparing a CdS thin film material according to claim 1, characterized in that: The hydrothermal treatment temperature is 100°C to 120°C, and the hydrothermal treatment time is 6h to 8h.
3. The method for preparing the CdS thin film material according to claim 1, characterized in that: The cadmium-containing precursor solution is a cadmium acetate dihydrate aqueous solution.
4. The method for preparing the CdS thin film material according to claim 1, characterized in that: The concentration of the cadmium-containing precursor solution is 0.005 mol / L to 0.01 mol / L.
5. The method for preparing the CdS thin film material according to claim 1, characterized in that: The sulfur-containing precursor solution is an aqueous solution of thioacetamide.
6. The method for preparing a CdS thin film material according to claim 1, characterized in that: The concentration of the sulfur-containing precursor solution is 0.005 mol / L to 0.01 mol / L, and the volume ratio of the cadmium-containing precursor solution to the sulfur-containing precursor solution is 1:1 to 1.
5.
7. The method for preparing a CdS thin film material according to claim 1, characterized in that: The substrate is conductive glass, silicon substrate or polymer flexible substrate.
8. A CdS thin film material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the CdS thin film material according to claim 8 in photocatalytic degradation of organic matter.